AN EVALUATION BY THE TEACHERSFOR THE UNITS OF THE EDUCATION PROGRAMME FOR WESTERN MUSIC’S CHORUS TRAINING - Ebru TEMİZ (Fırat University, 2019)
ABSTRACT The aim of this study is to exam the education programme of the chorus training in the syllabus of the Music Department of the Fine Arts and Sport High Schools since its foundation, and to specify the teachers’ ideas about the efficiency of the latest Western Music Chorus Training Lesson in terms of its units in 12th Classes. The sample space of the study has been determined as 11 Fine Arts and Sport High Schools by using a descriptive method. The data collection tool has comprised of 46 survey questions in the study and the reliability coefficient (Cronbach Alpha) has been found as .87 In terms of the statistical analysis, the descriptive statistical analysis techniques in the SPSS 16 Packaged Software have been used. Consequently, in the study, it has been come to the conclusion that the education programme for western music’s chorus training in the 12th Classes is not efficient in the practise in terms of its units.